2022
DOI: 10.3390/metabo12121166
|View full text |Cite
|
Sign up to set email alerts
|

p-Coumaric Acid Nanoparticles Ameliorate Diabetic Nephropathy via Regulating mRNA Expression of KIM-1 and GLUT-2 in Streptozotocin-Induced Diabetic Rats

Abstract: Diabetic nephropathy (DN) has become a leading cause of end-stage renal failure worldwide. The goal of the current study was to examine the protective effects of chitosan-loaded p-Coumaric acid nanoparticles (PCNPs) in nephrotoxicity induced by streptozotocin (STZ). Because of the antidiabetic, anti-inflammatory, and antioxidant properties of PCNPs, the development of DN may be considerably decreased. In this study, the rats received a single intraperitoneal injection (i.p.) of STZ (45 mg/kg) to induce DN. PCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…NAG, with a molecular weight of 130,000, is not easy to filter by the glomerulus. However, when the renal convoluted tubules are damaged, lysozyme will release a large amount of NAG, resulting in a significant increase in NAG in urine ( 21 ). OPN, one of the proinflammatory cytokines, was observed to be upregulated in the kidneys of diabetic animals and patients with nephropathy ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…NAG, with a molecular weight of 130,000, is not easy to filter by the glomerulus. However, when the renal convoluted tubules are damaged, lysozyme will release a large amount of NAG, resulting in a significant increase in NAG in urine ( 21 ). OPN, one of the proinflammatory cytokines, was observed to be upregulated in the kidneys of diabetic animals and patients with nephropathy ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study reported that IL-6 is positively expressed in STZ-treated renal tissues. On the other hand, nephropathic rats treated with chitosan-loaded p -coumaric acid nanoparticles (PCNPs) showed a considerable reduction in IL-6 in comparison with nephropathic rats [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The technique developed by Burgi et al . (1988) was used to assess insulin levels ( Venkatesan et al ., 2022 ). Hemoglobin (Hb) and glycated hemoglobin A1c (HbA1c) ( Trinder, 1969 ), urea, creatinine, total protein, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, triglycerides, cholesterol, very-low-density lipoprotein (VLDL), serum glutamic-oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), alkaline phosphatase (ALP), and C-reactive protein (CRP) were assessed in all test animals, utilizing commercially accessible tests obtained from the Egyptian Company for Biotechnology (Spectrum Diagnostics, Cairo, Egypt).…”
Section: Methodsmentioning
confidence: 99%